2004
DOI: 10.1161/01.res.0000109413.57726.91
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Induced Activation of Matrix Metalloproteinase-7 Promotes Vasoconstriction Through the Epidermal Growth Factor–Receptor Pathway

Abstract: Abstract-Matrix metalloproteinase (MMP)-dependent shedding of heparin-binding epidermal growth factor (HB-EGF) and subsequent activation of the EGF receptor (EGFR) in the cardiovasculature is emerging as a unique mechanism signaling growth effects of diverse G protein-coupled receptors (GPCRs). Among these GPCRs are adrenoceptors and angiotensin receptors that contribute to the pathogenesis of hypertension through their vasoconstrictive and growth effects. Focusing on ␣ 1b -adrenoceptors, we suggest here tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(176 citation statements)
references
References 27 publications
14
160
1
1
Order By: Relevance
“…ligands cleaved by MMPs, is also described [13,14]. Finally, the cisplatin-induced cytotoxicity seems to be closely associated with the increased production of reactive oxygen species (ROS) [15] and ROS contribute to cell death partly through effects on various cellular signalling pathways, including the mitogen-activated protein kinase (MAPK) pathway [16].…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -4mentioning
confidence: 99%
See 1 more Smart Citation
“…ligands cleaved by MMPs, is also described [13,14]. Finally, the cisplatin-induced cytotoxicity seems to be closely associated with the increased production of reactive oxygen species (ROS) [15] and ROS contribute to cell death partly through effects on various cellular signalling pathways, including the mitogen-activated protein kinase (MAPK) pathway [16].…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -4mentioning
confidence: 99%
“…An alternative mechanism to p38/MAPK, for EGFR transactivation, is the autocrine/paracrine release of soluble EGF ligands [56]. HB-EGF, epiregulin, and TGF-α can activate EGFR; these ligands are synthesized as transmembrane proteins (proforms) and cleaved by metalloproteases to yield soluble forms, thereby binding and leading to EGFR activation [13,14]. Indeed, we detected a baseline MMP-2 activity in conditioned media from PC Cl3 cells, and such activity, and MMP-2 protein expression, increased in a time-dependent manner after cisplatin treatment (Fig.…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -16mentioning
confidence: 99%
“…We have identified MMP-2, MMP-7, ADAM-12 and ADAM-17/TACE as mediators of angiotensin II-induced hypertensive cardiac disease. We have also found that gene expression of these metalloproteinases changes throughout disease development [16,36,[40][41][42]. Moreover, some MMPs and ADAMs (such as MMP-7 and ADAM-17) appear to regulate others (such as MMP-2 and ADAM-12).…”
Section: Gpcr Signaling Through Mmps and Adams: A Clock For Disease Dmentioning
confidence: 69%
“…Another non-ECM acute action of MMPs and ADAMs is shedding of membrane-anchored ligands of receptors such as epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) to transactivate intracellular signaling of growth via the MAPK cascade. Thus, metalloproteinases modulate MAPK signaling to help maintain agonist-induced vascular tone and signaling of hypertrophic growth [36].…”
Section: Cleavage Of Receptor Ligandsmentioning
confidence: 99%
“…transforming growth factor-β (TGF-β)), cell surface receptors (e.g. β2-adrenergic receptor, vascular endothelial growth factor receptor-2 (VEGFR-2), insulin receptor) and extracellular matrix components [2][3][4][5][6][7][8][9][10]. We review here emerging evidence that MMPs and ADAMs are key mediators that might regulate one another (e.g.…”
Section: Introductionmentioning
confidence: 99%